2011
DOI: 10.1021/jf202583f
|View full text |Cite
|
Sign up to set email alerts
|

Biofortification of Tomato (Solanum lycopersicum) Fruit with the Anticancer Compound Methylselenocysteine Using a Selenocysteine Methyltransferase from a Selenium Hyperaccumulator

Abstract: Methylselenocysteine (MeSeCys) is an amino acid derivative that possesses potent anticancer activity in animals. Plants that can tolerate growth on soils with high Se content, known as Se hyperaccumulators, do so by converting inorganic Se to MeSeCys by the enzyme selenocysteine methyltransferase (SMT). A cDNA encoding the SMT from a Se hyperaccumulator was overexpressed in tomato (Solanum lycopersicum). Transgenic plants were provided with selenite or selenate to the roots during fruit development, and liquid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
18
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
4
2

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 36 publications
3
18
0
1
Order By: Relevance
“…Agronomic Se-biofortification strategies to increase crop Se contents by using inorganic Se fertilizers have been successfully implemented in Finland and New Zealand ( Lyons et al, 2003 ; Hartikainen, 2005 ; Premarathna et al, 2012 ; Schiavon et al, 2013 ; Wang et al, 2013b ). Different forms of Se supplied for biofortification may result in different amounts and chemical forms of Se accumulated in plants ( Brummell et al, 2011 ; Schiavon et al, 2013 ; Pezzarossa et al, 2014 ). Due to chemical similarity to sulfate, selenate can be readily absorbed by plants, and plant leaves can accumulate substantial amounts of selenate, but much less selenite or SeMet ( De Souza et al, 1998 ; Zayed et al, 1999 ; Kikkert and Berkelaar, 2013 ).…”
Section: Developing Se-biofortified Agricultural Products For Human Hmentioning
confidence: 99%
“…Agronomic Se-biofortification strategies to increase crop Se contents by using inorganic Se fertilizers have been successfully implemented in Finland and New Zealand ( Lyons et al, 2003 ; Hartikainen, 2005 ; Premarathna et al, 2012 ; Schiavon et al, 2013 ; Wang et al, 2013b ). Different forms of Se supplied for biofortification may result in different amounts and chemical forms of Se accumulated in plants ( Brummell et al, 2011 ; Schiavon et al, 2013 ; Pezzarossa et al, 2014 ). Due to chemical similarity to sulfate, selenate can be readily absorbed by plants, and plant leaves can accumulate substantial amounts of selenate, but much less selenite or SeMet ( De Souza et al, 1998 ; Zayed et al, 1999 ; Kikkert and Berkelaar, 2013 ).…”
Section: Developing Se-biofortified Agricultural Products For Human Hmentioning
confidence: 99%
“…Yet, the range between beneficial and harmful concentration of Se is relatively narrow. In fact the World Health Organization (WHO) and the United States Department of Agriculture (USDA) recommend a daily intake of 55–200 μg Se in regular adults ( USDA, 2012 ) to reduce, for instance, the incidence of prostatic and lung cancer ( Brummell et al, 2011 ; Dennert et al, 2011 ). Doses greater than 400 μg Se per day on the other hand, might produce toxic effects, resulting in pathological conditions ( Rayman, 2008 ; Rayman, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…The SMT gene is inducible by selenate in broccoli (Lyi et al, 2005 ) and has been confirmed as the key to Se-tolerance in Se-accumulating plants (Neuhierl and Bock, 1996 ; Neuhierl et al, 1999 ). Its over-expression in non-Se accumulator species, such as tobacco and tomato, has been shown to convert such plants into Se-accumulators with up to 25% of the Se in these plants found as MeSeCys (McKenzie et al, 2009 ; Brummell et al, 2011 ).…”
Section: Selenium In Brassicalesmentioning
confidence: 99%